Strategi Pengembangan Wisata Budaya Keraton Sumenep di Kelurahan Pajagalan, Kecamatan Kota Sumenep, Kabupaten Sumenep, Jawa Timur - Poerwati, Titik; Desderius, Kevie; Lidya Subnafeu, Eglantyne; Parmanes, Ester; Rangga Saputra, Dityanda; Aprilianus Dapa, Yohanes (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2023)
The Sumenep Palace is one of the leading cultural tourism destinations in Sumenep Regency, because it has interesting cultural values. However, the Sumenep Palace still finds various obstacles in its journey such as low visitor interest, lack of interesting tourism activities, and incomplete facilities so that this cultural tourism has not optimally provided a positive impact, especially economically to the community. Therefore, a study is needed to analyse the characteristics of the Sumenep Palace tourism area and its development strategy. To achieve this goal, a descriptive analysis of cultural tourism characteristics in the tourist area consisting of attractions, amenity, accessibility, accommodation, activities and cultural values, as well as analysis of internal and external factors in the tourist area such as strengths, weaknesses, opportunities and threats. Based on the results of the analysis, it is known that the characteristics of the Sumenep Palace area based on six research variables are as follows; the attraction factor consists of historical buildings, palace museums, and historical heritage icons. The amenity factor consists of an information centre, and a souvenir centre (UMKM). In terms of accessibility, the ease of reaching the Sumenep Palace is very good, because it is right in the city centre, can be reached through various directions, and road conditions that can be passed by all types of vehicles, its accommodation factors consist of homestays and hotels around the palace, then tourist activities that can be done in the Sumenep Palace tourist area are exploring the palace location and visiting the palace museum. For its cultural value consists of the history and tradition of the Sumenep Palace. Based on the results of the SWOT analysis, it is known that the development strategy carried out is to focus on overcoming weaknesses to seize opportunities. So formulated three development strategies namely optimisation of completeness of tourist facilities, local economic development, and procurement of interesting tourist activities.